Prophylactic relationship between mental health disorder symptoms and physical activity of Royal Canadian Mounted Police Cadets during the cadet training program - Teckchandani, Taylor; Krakauer, Rachel L.; Andrews, Katie L.; Neary, J. Patrick; Nisbet, Jolan; Shields, Robyn E.; Maguire, Kirby Q.; Jamshidi, Laleh; Afifi, Tracie O.; Lix, Lisa M.; Sauer-Zavala, Shannon; Asmundson, Gordon J. G.; et al. (Frontiers in Psychology, 2023)
Objective: Royal Canadian Mounted Police report experiencing extremely frequent potentially psychologically traumatic events (PPTE) (Carleton et al., 2019). In a recent study (R. Nicholas Carleton et al., 2018), approximately half of participating RCMP screened positive for one or more mental disorders, which is approximately five times the diagnostic proportion for the general Canadian population (Pelletier et al., 2017). Increased reporting of mental health symptoms been linked to PPTE exposures (Carleton et al., 2019). Programs promoting physical activity may be useful interventions to supplement or pair with mental health interventions, providing anxiolytic, antidepressant, and stress-buffering effects. The current study was designed to assess the relationship between physical activity behaviours and reported mental health disorder symptoms of cadets during the Royal Mounted Canadian Police (RCMP) Cadet Training Program (CTP). Methods: The study included data from 394 cadets (76.1% male). An analysis of variance (ANOVA) and a series of t-tests were used to assess for several differences across sociodemographic groups. Bivariate Spearman’s Rank correlations were performed between the average number of active calories burned per day, as recorded by Apple Watches, and changes in self-reported mental health disorder symptoms (i.e., Generalized Anxiety Disorder [GAD], Major Depressive Disorder [MDD], Posttraumatic Stress Disorder [PTSD], Social Anxiety Disorder [SAD]. Alcohol Use Disorders [AUD], Panic Disorder [PD]) from pre-training (starting the CTP) to pre-deployment (completing the CTP) 26 weeks later. Results: There were statistically significant inverse correlations between physical activity and self-reported mental health disorder symptom scores during CTP. Cadets who performed more physical activity from pre-training to pre-deployment had statistically significantly greater decreases in symptoms of GAD (R2 = -.472, p < .001), MDD (R2 = -.307, p < .001), PTSD (R2 = -.343, p < .001), and AUD (R2 = -.085, p < .05). There was no statistically significant relationship between physical activity and changes in PD symptoms (R2 = -.037, p > .05). Conclusion: There was evidence of an inverse relationship between mental health disorder symptom scores and physical activity during the 26-week CTP. The results were consistent with extant evidence that exercise can be an important tool for reducing mental health disorder symptoms.